Effect of Communication and Work Environment on Employee Performance - Ilham, Rachmad; Budianto, Shintya Nur Agustin (Journal of Business Management and Economic Development, 2023)
This study aims to find out: (1) to find out that communication has a partial effect on employee performance at PT Astra Sedaya Finance Gresik Branch (2) to find out that the work environment has a partial effect on employee performance at PT Astra Sedaya Finance Gresik Branch (3) to know communication and work environment influences simultaneously on the performance of employees of PT Astra Sedaya Finance Gresik Branch. In this study using primary data, while the research method involves one dependent variable (employee performance), and two independent variables (communication and work environment). The population used in this study were all PT Astra Sedaya Finance Gresik Branch employees, totaling 45 people. The sampling method was carried out using a non-probability sampling method. The technique used is saturated sampling technique. Data collection methods used in this study were questionnaires, documentation and interviews. The analytical method uses validity test, reliability test, multiple linear analysis, coefficient of determination, t test, F test. Conclusion of the study: communication has a partial effect on the performance of employees of PT Astra Sedaya Finance Gresik Branch, this is evidenced by the tcount (3.9437) > ttable (2.01808) and a significant level of 0.000 is smaller than alpha 0.05. The work environment has a partial effect on the performance of employees of PT Astra Sedaya Finance Gresik Branch, this is evidenced by the tcount (3.580) > ttable (2.01808) and a significant level of 0.000 is smaller than alpha 0.05. Communication and the environment simultaneously influence the performance of PT Astra Sedaya Finance Gresik Branch employees. This is evidenced by the value of Fcount (46.655) > Ftable (3.21) and a significant level of 0.000 is smaller than alpha 0.05.